Assess of biomass co-firing under oxy-fuel conditions on Hg speciation and ash deposit formation. (1st March 2018) - Contreras, M.L.; Ganesh, N.; Rodilla, I.; Bahillo, A.
Highlights: In coal case, oxy-firing enhances Hg capture on the finest particles. Main affection of oxy-conditions on Hg fate is observed for cofiring processes. Oxy-cofiring increases Hg oxidation in the flue gas phase. At low temperatures, HCl(g) fraction is decreased in oxy-cofiring vs air. Oxy-fuel combustion reduces chloride deposition versus sulphates formation. Abstract: In the last years oxy-fuel combustion has been seen as an attractive method for oxygenated fuels, such as biomass, for controlling simultaneously the excess of heat arising from coal combustion and flue gas emissions (CO2, NOx, SO2 …). However there is a lack of information with respect to the fate of other toxic pollutants found in trace concentrations, such as mercury, in oxy-fuel processes operating with biomass fuels. In addition, the modified conditions and flue gas composition leads to more corrosive environments which needs of previous evaluation to minimize possibly damaging processes in the boilers, furthermore in case of employing biomass of high alkaline compounds contents. The present work evaluates the effect of oxy-combustion processes of sub-bituminous coal and coal/ biomass (thistle) blends on mercury partitioning and speciation, under both air and different oxy-fuel combustion atmospheres, by means of a bubbling fluidized bed combustor at laboratory scale. HSC Chemistry 6.1 was supplemented for the interpretation of the experimental results and for the analysis of ash deposits formation. Hg speciation was seen to be more affected by oxy-fuel combustion during the co-firing tests than in coal combustion, with an increment in Hg oxidation at low temperatures (T < 350 °C) and mainly for oxygen concentrations over 30% v/v. This effect is highly related to variations produced in chlorine speciation in the oxy-fuel atmospheres, in which ash deposition and corrosion modifications were seen to be also involved, with a reduction of the chlorinated species against an increased in the sulphated compounds concentration.